Pelatihan Karya Tulis Ilmiah Untuk Mengembangkan Pemikiran Komputasi Mahasiswa - alfina fadzilah; M. Fathur Izzurrohman; Santika Lya Diah Pramesti (Jurnal Pengabdian Inovasi Masyarakat Indonesia, 2023)
Scientific writing is something that is familiar to students. Scientific writing is one of the main characteristics of university academic activities, namely in the form of theses, theses, dissertations, articles, papers, and research reports. In addition, writing scientific papers is also one of the requirements for students to obtain an academic degree from higher education. However, the facts in the field and some results from previous studies show that the ability to write scientific papers in students is still low. Therefore, the results of the agreement on the work program of the Mathematics Tadris Student Association of UIN KH. Abdurrahman Wahid Pekalongan, which provides opportunities for students to develop computational thinking through writing scientific papers. This training was carried out in one meeting and the speakers thoroughly discussed the writing of scientific papers using the lecture and discussion methods. The results of this training students can write scientific papers in the form of journals in groups and will be submitted at the SANTIKA (National Seminar on Tadris Mathematics) on September 16, 2022. Thus, these results show that this training activity is effective in helping students to improve and develop students' computational thinking and scientific writing skills.